2012
DOI: 10.1245/s10434-012-2327-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interval between Neoadjuvant Chemoradiotherapy and TME for Locally Advanced Rectal Cancer on Pathologic Response and Oncologic Outcome

Abstract: In this retrospective analysis, there seems to be an association between a longer interval after neoadjuvant chemoradiotherapy and complete pathologic response without affecting postoperative morbidity and length of hospital stay, and with no detrimental effect on oncologic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 29 publications
5
93
2
3
Order By: Relevance
“…Some studies have reported increased rates of tumour down-staging when a longer interval between CRT and surgery is employed [21][22][23]. Other studies do not, however, support these findings [2], and a data from definitive large RCTs are therefore awaited with interest [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported increased rates of tumour down-staging when a longer interval between CRT and surgery is employed [21][22][23]. Other studies do not, however, support these findings [2], and a data from definitive large RCTs are therefore awaited with interest [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This interval in the majority of older studies was between 6 to 7 weeks, while in our study, about 64% underwent surgery 8 weeks or later after the completion of radiotherapy (RT). There are numerous studies indicating that increasing interval between the completion of RT and surgery leads to an increase in pCR in rectal cancer (18). The mean number of resected lymph nodes in our study was 5.2, while this number is usually more than 6…”
Section: Discussionmentioning
confidence: 44%
“…In one study evaluating the timing of rectal resection after neoadjuvant chemoradiation therapy, there was no difference in leak rate between patients who had earlier vs later surgery following therapy (,7 vs .7 weeks). 56 In a similar study on esophagectomy patients, there was also no difference in earlier vs later surgery following chemoradiation therapy either (,8 vs .8 weeks). 57 From these studies, we may be able to conclude that longer wait times are unlikely to reduce the risk of anastomotic leakage.…”
Section: Steroids/immune Modulatorsmentioning
confidence: 88%